PTH-036 Intra-ductal covered self-expanding metal stents are not just for the management of post-transplant anastomotic strictures. (June 2019) - Keane, Geri; Warner, Ben; Reffitt, David; Devlin, John; Harrison, Phillip; Joshi, Deepak
Abstract : Introduction: Traditional fully covered self-expanding metal stents (FCSEMS) can have poor durability in certain situations e.g. post transplant anastomotic strictures, leading to proximal or distal stent migration. Novel intra-ductal FCSEMS have been developed with an antimigration waist, short stent length and removal wires that are deployed in the duodenum to allow easy removal. These stents have improved the management of post-transplant anastomotic strictures, substantially decreasing the number of ERCPs these patients require and are now becoming the preferred stent in this situation in a number of transplant centres globally. Non-transplant indications for this stent have rarely been described. Methods: Case series of novel indications for ID-FCSEMS from a tertiary referral HPB/Liver Transplant centre. Results: 10 ID-FCSEMS were inserted in 9 patients for a range of indications (bile leak following transplant (3) or hepatectomy (1), bile leak following spontaneous perforation of the bile duct during acute pancreatitis, stricturing due to bile duct trauma post laparoscopic cholecystectomy (2), Mirizzi syndrome or choledochal varices). Five stents were inserted into the CHD/CBD and 5/10 into the proximal IHD/hilum. Median age of the patients was 51 years, and the majority were female (55%). Five patients had had a previous ERCP and plastic stent, which had been unsuccessful. 90% (9/10) of the stents inserted were 8×40 mm, with a single 10×40 mm stent inserted in one case. A sphincterotomy was performed in 60% cases and 30% of strictures were balloon dilated prior to stent insertion. Clinical resolution of the leak or stricture was seen in 100% of cases. There were no associated episodes of stent migration or post ERCP pancreatitis. All stents were removed without any difficulty. No patients required a further ERCP or intervention following ERCP with ID-FCSEMS insertion. Conclusion: This novel ID-FCSEMS is associated with high rate of clinical success in a range of clinical indications, over and above the management of post-transplant anastomotic strictures. There were no associated adverse events. As a result, there are growing number of applications for this novel stent.